Influence of dolphin-watching tourism vessels on the whistle emission pattern of common dolphins and bottlenose dolphins - Silva, Ana Maria Conceição Alves da (2022)
Over the last few years there has been a significant increase in the number of dolphin-watching boats in the Algarve (Portugal), which my lead to short- and long-term impacts on the target species (e.g., common dolphin, bottlenose dolphin). In recent decades there has been a greater interest in the potential effects of anthropogenic noise on marine mammals, given the important role that sound plays in the vital functions of these organisms. Several changes in the behavior and energy expenditure of cetaceans have been documented, including impacts in the vocalization parameters of dolphins, reduction in the communication range of whistles and increase energy expenditure. In this study, the whistles characteristics of common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) were analyzed in the presence and absence of dolphin-watching tour boats to detect potential impacts in the vocalization of dolphins. Field recordings of common dolphin and bottlenose dolphin whistles were made from June to September 2022, using a calibrated system. Dolphin behavior and group size were recorded, as well as the number of boats in a 300 m radius. A total of 15h of acoustic recording was analyzed. Overall, these results showed a significant increase in start, low and high frequency on both species when exposed to the presence of one or more dolphin-watching tour vessels. However, when analyzing the whistles, it was possible to observe a reduction in the number of inflection points in the presence of the same vessels. These changes can be a dolphin strategy to avoid sound masking and increase of energy expenditure. These findings indicate that anthropogenic impact in the form of dolphin-watching tour vessels can influence the vocalization parameters of dolphins and such changes could have an impact if they reduce the communication range of whistles or increase energy expenditure.